2019
DOI: 10.1016/j.cct.2019.105835
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor versus placebo for the reduction of vaso-occlusive crises in pediatric sickle cell disease: Rationale and design of a randomized, double-blind, parallel-group, multicenter phase 3 study (HESTIA3)

Abstract: Background: An unmet need for therapies exists to reduce sickle cell disease (SCD) complications in pediatric patients. Activated platelets contribute to the formation of cellular aggregates during sickling and vaso-occlusive crises (VOCs). Ticagrelor is an oral, direct-acting, and reversible adenosine diphosphate P2Y 12 receptor antagonist that inhibits platelet activation and aggregation. Although ticagrelor was well tolerated in two phase 2 studies in children and young adults with SCD, larger and longer-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Differences in definitions can make between-study comparisons difficult; however, because pain and ACS are the two most common reasons for hospitalization, often coexist, and together represent the major burden in sickle cell disease, combining these clinical events provides a better estimate of disease burden, which is the primary objective of this study. Additionally, some recently conducted clinical trials have used this description [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in definitions can make between-study comparisons difficult; however, because pain and ACS are the two most common reasons for hospitalization, often coexist, and together represent the major burden in sickle cell disease, combining these clinical events provides a better estimate of disease burden, which is the primary objective of this study. Additionally, some recently conducted clinical trials have used this description [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, no safety concerns were raised from treating pediatric patients with a broad range of single and repeated doses of ticagrelor during the study. The potential of ticagrelor to impact SCD‐related pain crises warrants further evaluation in this population, and a phase 3 study (HESTIA3) is planned …”
Section: Discussionmentioning
confidence: 99%
“…27 Information garnered from recent studies of other novel therapies, including SUSTAIN (crizanlizumab), DOVE (prasugrel), HESTIA (ticagrelor), and several others have demonstrated that there are still a significant proportion of patients who either are not taking HU, or experience breakthrough VOCs while taking HU. [28][29][30] Chronic transfusion therapy Chronic transfusion therapy is used primarily to reduce the risk of stroke in high-risk individuals with SCD. 31,32 However, it can also be used to reduce the levels of circulating sickled RBCs, and thereby decrease the number of VOCs when used as prophylactic therapy.…”
Section: Hydroxyureamentioning
confidence: 99%
“… 27 Information garnered from recent studies of other novel therapies, including SUSTAIN (crizanlizumab), DOVE (prasugrel), HESTIA (ticagrelor), and several others have demonstrated that there are still a significant proportion of patients who either are not taking HU, or experience breakthrough VOCs while taking HU. 28 30 …”
Section: Current Strategies To Reduce the Occurrence Of Vocsmentioning
confidence: 99%